Return On Asset The Impact of Current Ratio, Debt To Equity Ratio and Company Size - Hertina, Dede; Aprillia, Prilly; Julyvia Rulian, Irena (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the influence of variable Current Ratio, Debt To Equity Ratio, Firm Size to Return On. The population of this research is the entire company contained in the sub-sector Food and Beveragelisted on the Indonesia Stock Exchange period 2014-2018. The research samples that match with criteria used puposive sampling consist of 9. The type of this researcg is quantitative with descriptive and verification research method. The data analysis method used is the analysis of the Data regression panel (Fixed Effect). Simultaneously Research Results Current Ratio, Debt To Equity Ratio and Firm Size variable affect the Return On Asset. Partially Current Ratio and Debt To Equity Ratio variables have no affect to Return On Asset, and Firm Size variables have significant negative impact on Return On Asset.